FRI0101 Ra in male carpenters: occupational wood dust exposure increases acpa and rf seropositivity and significantly raises rf titres. (15th June 2017) - Bellis, K; Whallett, M; Murphy, D; Hutchinson, D
Abstract : Background: Wood dust has been hypothesised as a trigger in RA. Exposure may activate peptidyl arginine deaminase through exposure to silica and carbon nanoparticles, 1 stimulating RF autoantibody production. 2 Though non-silica dusts have shown increased RA risk in construction workers, wood dust exposed individuals were excluded from analysis in a recent large registry study. 3 Objectives: To analyse the autoantibody status of male RA wood workers in Cornwall, UK, compared to matched RA controls with no occupational dust or fume exposure. Methods: All male RA patients were sent an occupational questionnaire, detailing current occupation, last occupation (if retired) and other occupations for >1 year. Telephone follow up was completed to minimise missing data. 41/720 (6%) patients died during the study period (22 months). 39/720 (5%) were excluded due to incomplete data. 147/640 (23%) had exposure to wood dust including other dust co-exposures, with 44/147 (30%) indentifying wood dust as their primary occupational exposure as carpenters, approximately seven times higher than expected given UK employment census data. This cohort was matched to 102 RA controls with no dust or fume exposure for age +/- 5 years, sex and index of multiple deprivation (IMD) +/- 1 decile. RF titres were compared via 2 tailed Mann Whitney U test, and ACPA seropositivity was compared using a Z test of 2 proportions. Results: No significant differences were seen in median age between woodworker cases (median 59 years IQR 50–63), and controls (median 58 years IQR 48–65). Woodworker never smokers demonstrated significantly higher seropositivity rates for both RF and ACPA than respective controls, and RF titres were significantly higher amongst woodworkers irrespective of smoking (Table 1 ). Median smoking rates were not significantly different between cohorts: woodworkers median pack years 23.5 (IQR 14.75–36), control median pack years 20.5 (IQR 10.25–32.75). Conclusions: Wood dust exposed RA patients are more likely to be seropositive. Sequential environmental insults of smoking and wood dust exposure have an additive effect on rheumatoid factor levels, conferring increased disease severity. Further studies are needed to determine if occupational wood dust exposure causes RA. References: Murphy D, Sinha A, Hutchinson D. Wood Dust: A Trigger for Rheumatoid Arthritis? Am J Med 2015;128:e35. Hubbard R, Lewis S, Richards K, Johnston I, Britton J. Occupational exposure to metal or wood dust and aetiology of cryptogenic fibrosing alveolitis. Lancet 1996;347:284–9. Blanc PD, Jarvholm B, Toren K. Prospective risk of rheumatologic disease associated with occupational exposure in a cohort of male construction workers. Am J Med 2015;128:1094–101. Acknowledgements: Cornwall Arthritis Trust. Disclosure of Interest: None declared